Vitreoretinal disease : a manual for diagnosis and treatment - Morse, Peter H (Year Book Medical Publishers, 1979)
A guidebook that focuses on the diagnosis and treatment of vitreoretinal diseases. Intended for professional public.
Keywords: oftalmologie; Vitreous Body; sklivec; nemoci retiny; Retinal Diseases